Los miedos infantiles y el rendimiento académico en los niños del nivel de inicial 2 paralelo “c” del centro de educación inicial lic. “Alfonso Chávez”, parroquia Lizarzaburu, cantón Riobamba, provincia de Chimborazo. Año lectivo 2014-2015 - Caicedo Ayovi, Carlos Javier (2016)
This project is related to the children's fears and the academic performance of children, since it offers to teachers and parents, useful tools that will benefit future children of initial education centre "Alfonso Chávez" to overcome their fears and at the same time improve their academic performance. The theme of the project has much significance, since fears are normal human beings during their life; But if it fails to compare to certain ages may be a trigger for many problems. That took the initiative to carry out this research, with the general aim: to determine the incidence of children's fears and the academic performance in the children of the level of initial 2 parallel, "c" of the Center for education initial Lic. "Alfonso Chávez," Parish Lizarzaburu, canton Riobamba, Chimborazo province. Academic year 2014-2015; through the implementation of a field work, by applying the survey to the teacher, and the observation form to children. As a solution to the problem in question was designed a tutorial in order to overcome the fears of the children of the above-mentioned educational institution and contribute to the improvement of academic achievement called "Overcoming my fears I am happy". The results allowed to meet the research objectives, reaching the hypothesis testing positively since the teachers agreed that fears significantly affect the academic performance of children. Finally the conclusions and recommendations were presented